The Development of Cold Chain System on Fresh Tuna Fish (Euthynnus affini) for Fish Retailer - Wiranata, Ketut; Widia, I Wayan; Budisanjaya, I Putu Gede (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This aims of this research were to determine the effect of the use of an ice cooling media with the addition of salt and ice cooling media comparisons with the raw materials of fish on the quality of fresh fish. This research used factorial experimental design with two factors, namely the use of ice cooling media with the addition of salt and ice cooling media comparison with raw fish. Factors adding salt consists of four treatments, without the addition of salt, the addition of salt 10%, 12.5%, and 15% of the amount of ice used. While factors ice cooling media comparisons with the raw materials of fish is 1:1 and 1:1.5. Parameters of observation in this research was the long time cold chain system, pH, organoleptic appearance, organoleptic odor, organoleptic texture, histamine, TVB, TPC. The results of this research indicating that the use of an ice cooling media with the addition of salt and ice cooling media comparisons with the raw materials of fish, as well as the interaction between treatments giving effect of good on the quality of fresh fish. The interaction addition of salt as much as 15% and the ratio of 1:1 gives the best results on the quality of fresh fish with characteristics, long time cold chain system of 11 hours and 24 minutes, the pH value of 6.25, a fresh appearance (8,4), the smell of fresh (8.1), the texture of fresh (8.0), histamine 7,90 mg / 100 g, TVB 10,40 mg / 100 g, TPC 7,4x103 colonies/g.